'Honey pot' rural enterprise hubs as micro-clusters: Exploring their role in creativity-led rural development. (November 2021) - Merrell, Ian; Rowe, Frances; Cowie, Paul; Gkartzios, Menelaos
Rural enterprise hubs are physical infrastructures designed to help rural businesses access tangible and intangible benefits. They generally operate within two main business models: 'Honey Pots' (i.e. targeting business-to-customer tenants) and 'Hives' (i.e. targeting business‐to‐business tenants). This paper focuses on the former type, Honey Pot hubs, which are best suited to tenants who sell their products/services directly to the general public, such as some creative sectors, retail and tourism. Honey Pot hubs are designed to cater to such needs by attracting footfall to the space, providing cafes and facilities for the general public and hosting events. This paper explores how these Honey Pot hubs contribute to rural and regional development, through the creative practices of their tenants. The paper draws on qualitative interviews with Honey Pot managers and tenants in remote rural locations of the North East of England. The findings are useful for Hub practitioners, policy makers and rural creative businesses who want to develop similar initiatives in their locales.